Periodontal disease and 'oral health' in the past: new insights from ancient Sudan on a very modern problem. - Rebecca Whiting; Daniel Antoine; Simon Hillson (Dental Anthropology Association, 2019)
As one of today's major oral health issues, periodontal disease affects populations worldwide. Here, methods used to record its past prevalence are reviewed, including the problems associated with the use of measurements to record bone loss. Clinical and bioarchaeological research offers strong support for the Kerr method that records interdental septum morphological changes as a means of identifying gingivitis and periodontal disease. Using Kerr's approach, four assemblages from Sudan dating to the Neolithic, Kerma and Medieval periods are examined to track the progression of the disease through time. Results show a significantly lower prevalence of periodontal disease and a limited distribution across the mouth in the Neolithic period. Significant differences were found between the sexes at the Medieval sites, which were not present at the Neolithic and Kerma sites. With no patient history and the cumulative effects of a dynamic and episodic disease - only a snapshot of which is captured at death - the concept of 'oral health' may be hard to apply in archaeological remains. As suggested by Kerr, it at best provides an insight into the periodontal status at death. Here, this 'snapshot' reveals differences across the mouth, over time and between sexes.